PENCATATAN TRANSAKSI DAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS SPREADSHEET PADA BENGKEL DIKA MOTOR KABUPATEN AGAM - Asma Nadya Suwandi; Endang Afriyeni; Sepri Neswardi (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Abstract The purpose of this study is to assist business owners in providing detailed and systematic financial statements using Microsoft Excel. The object of research is a service company, namely Dika Motor Workshop in Agam Regency. This type of research in writing this thesis is quantitative research by processing the figures in the form of transaction results and the analytical method used is descriptive method, which explains and describes the steps in the process of recording transactions and preparing financial statements in accordance with the accounting cycle using Microsoft Excel. Based on the results of interviews and observations by the authors of the spaciousness, it was found that the workshop owner did not yet have a detailed recording and compilation of financial statements so that the owner could not yet see what the financial position was and separate personal wealth from company property. This research succeeded in designing the recording of transactions, and financial statements in the form of profit and loss statements, reports of changes in capital and balance sheet at a spreadsheet-based Dika Motor workshop using Microsoft Excel in the June 2019 period. Keywords: transaction, financial statements, spreadsheets, microsoft excel 2010, Dika Motor workshop